2023
DOI: 10.1111/ejss.13439
|View full text |Cite|
|
Sign up to set email alerts
|

Sustainable soil management: Soil knowledge use and gaps in Europe

Martin Hvarregaard Thorsøe,
Saskia Keesstra,
Maarten De Boever
et al.

Abstract: Soils are the foundation of agricultural production, ecosystem functioning and human well‐being. Bridging soil knowledge gaps and improving the knowledge system is crucial to meet the growing EU soil policy ambitions in the face of climate change and the ongoing trend in soil degradation. The objective of this article is to assess the current state of knowledge, knowledge use and knowledge gaps concerning sustainable soil management in Europe. This study is based on interviews with 791 stakeholders and 254 res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
(65 reference statements)
1
5
0
Order By: Relevance
“…Some experts mentioned that the integration of the farmer and farm advisor community with the soil research community could be improved to address existing knowledge gaps. This observation aligns with the results of a survey that consulted more than 300 soilrelated stakeholders from across Europe (Thorsøe et al, 2023;Vanino et al, 2023). Contrastingly, Strauss et al (2023) found that lack of knowledge was a less relevant barrier to adopt sustainable soil management practices in Germany.…”
Section: Barriers To the Adoption Of Conservation Agriculturesupporting
confidence: 76%
See 3 more Smart Citations
“…Some experts mentioned that the integration of the farmer and farm advisor community with the soil research community could be improved to address existing knowledge gaps. This observation aligns with the results of a survey that consulted more than 300 soilrelated stakeholders from across Europe (Thorsøe et al, 2023;Vanino et al, 2023). Contrastingly, Strauss et al (2023) found that lack of knowledge was a less relevant barrier to adopt sustainable soil management practices in Germany.…”
Section: Barriers To the Adoption Of Conservation Agriculturesupporting
confidence: 76%
“…The reported impacts of soil management practices (Supplementary Information II) allowed three key observations to be made: First, a greater number of soil management practices were reported to tackle the more widespread soil challenges (i.e., enhancing nutrient use efficiency and retention, reducing soil erosion, enhancing soil structure, enhancing SOC content, and enhancing water storage capacity) compared to more regional soil challenges. The regional soil challenges were: avoiding soil acidification and salinization, avoiding peat degradation, and avoiding soil sealing (see Thorsøe et al (2023) and JRC (2015) for the distribution of soil challenges across Europe). Second, the three soil challenges of reducing N 2 O and CH 4 emissions from soils, reducing soil contamination, and enhancing soil biodiversity were reported to be tackled by relatively few practices (less than 21% of the practices where the impacts were assessed), and many knowledge gaps on impact of soil…”
Section: Environmental Zonesmentioning
confidence: 99%
See 2 more Smart Citations
“…To reach the aims of programmes such as the EJP SOIL, it is nevertheless fundamental to ensure that all involved stakeholders-from researchers to endusers, practitioners and decision makers-understand the terminology used and can sufficiently disentangle a common meaning based upon the source of the terminology. Consequently, there is a need for a more effective communication, requiring a harmonization of different approaches, a common language with clear definitions (Carmen et al, 2018) and a better understanding of knowledge gaps in sustainable soil management (Thorsøe et al, 2023).…”
Section: Introductionmentioning
confidence: 99%